2016
DOI: 10.1093/jmammal/gyw128
|View full text |Cite
|
Sign up to set email alerts
|

Pika (Ochotona princeps) losses from two isolated regions reflect temperature and water balance, but reflect habitat area in a mainland region

Abstract: Although biotic responses to contemporary climate change are spatially pervasive and often reflect synergies between climate and other ecological disturbances, the relative importance of climatic factors versus habitat extent for species persistence remains poorly understood. To address this shortcoming, we performed surveys for American pikas (Ochotona princeps) at > 910 locations in 3 geographic regions of western North America during 2014 and 2015, complementing earlier modern (1994-2013) and historical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 80 publications
(112 reference statements)
0
40
0
Order By: Relevance
“…Pikas are typically easy ( p usually > 0.90) to detect (e.g., [42,51,56]), and we assume that to be the case in GNP because: 1) individuals in GNP generally construct and defend obvious haypiles; and 2) individuals use vocalizations both for conspecific attraction and for territorial announcement/defense, so these calls are often given when surveyors enter a talus patch. Although detectability can vary between regions and locations (e.g., lower at some anomalously low-elevation sites, described in [57]), and observer variability can influence results, our field crew received training and conducted trials to measure these factors. In GNP, repeated surveys by each member of the 2009 field crew revealed that the identity of the individual was not a significant predictor (multiple linear regression, F-test, p >> 0.05) of the number and type of pika signs observed nor home ranges estimated, with the exception of one individual who overestimated vocalizations and HRs [78].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pikas are typically easy ( p usually > 0.90) to detect (e.g., [42,51,56]), and we assume that to be the case in GNP because: 1) individuals in GNP generally construct and defend obvious haypiles; and 2) individuals use vocalizations both for conspecific attraction and for territorial announcement/defense, so these calls are often given when surveyors enter a talus patch. Although detectability can vary between regions and locations (e.g., lower at some anomalously low-elevation sites, described in [57]), and observer variability can influence results, our field crew received training and conducted trials to measure these factors. In GNP, repeated surveys by each member of the 2009 field crew revealed that the identity of the individual was not a significant predictor (multiple linear regression, F-test, p >> 0.05) of the number and type of pika signs observed nor home ranges estimated, with the exception of one individual who overestimated vocalizations and HRs [78].…”
Section: Methodsmentioning
confidence: 99%
“…princeps (14–34 m: [64]), because inaccuracy and variability both increase as distance increases, using ocular estimation; and 2) administering multiple, intensive field-crew training sessions–after these, we found consistency among our field crew in making these HR estimates (difference between individuals using multiple linear regression, F-test p >> 0.05 [78]). Improved accuracy could potentially be achieved by use of laser rangefinders to estimate distance of talus-patch dimensions ( sensu [57]) or by using remotely sensed data, as in [58], although the latter can be extremely inaccurate, as quantified in this study, and suffers from not accounting for talus that is not pika-appropriate (generally, when talus rock diameters are all <0.2 m or >1.0 m; [65]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has long been suspected that the thermal sensitivity of the American pika will ultimately threaten the species' viability in the face of climate change; such sensitivity has already been implicated in | 2521 population declines and local extirpations within the last decade (e.g., Beever, Perrine, et al, 2016;Jeffress, Rodhouse, Ray, Wolff, & Epps, 2013;Stewart et al, 2015Stewart et al, , 2017, including within NOCA itself (Johnston et al, in review). In fact, we recently provided physiological evidence of climate-induced stress in American pika populations at our sample sites (Waterhouse et al, 2017).…”
Section: Outlier Detectionmentioning
confidence: 99%